Analysis of RNA secondary structure by photochemical reversal of psoralen crosslinks. - Rabin, D (1979)
Aminomethyltrioxsalen (AMT), a psoralen, is known to cause interstrand crosslinks in double stranded nucleic acids. We have demonstrated the photochemical reversal of this reaction, and have used this result to develop a method for identification of specific sequences which are adjacent because of RNA secondary structure formation. E. coli 5S rRNA is used as a model system. We isolated and characterized a product that is derived from the stem region of 5S RNA.